Kegiatan Pengabdian Masyarakat Mengenai Deteksi Dini Masalah Gizi Di Sekolah Dasar Negeri 01 Ciherang, Cianjur - Yohanes Firmansyah; Farell Christian Gunaidi; Junius Kurniawan; Friliesa Averina; Hamzah Hamzah; Eric Hartono; Catherine Christiana Pranata (Universitas 17 Agustus 1945 Semarang, 2024)
The nutritional status of children significantly impacts their overall health and development, intertwined with socioeconomic factors. Adequate nutrition is essential for cognitive development and academic performance. Despite its importance, malnutrition remains prevalent among Indonesian children, with varying degrees of underweight, overweight, and obesity. This study utilized the PDCA method to screen nutritional status among students at SDN 01 Ciherang, West Java. Anthropometric measurements revealed diverse nutritional statuses, emphasizing the need for collaborative efforts among students, educators, and parents to implement interventions for healthier dietary habits and long-term health outcomes.